DERADICALISING RELIGIOUS EDUCATION - Irham Irham; Sansan Ziaul Haq; Yudril Basith (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2020)
This articles discusses deradicalization attempts in religious educational settings. It closely examines the roots of religious radicalism and offers the deradicalisation models in religious educational institutions. The discussion contributes to the current scholarship on the role of religious education in deradicalization programs and how create an Islamic educational institution that corfims and applies principles of multiculturalism. The paper particularly addresses the roles of teacher, the curriculum aspect of learning, and the translation of multiculturalism into Islamic education. Managerial aspect will be also included in the discussion. It further argues that the implementation of principles of multiculturalism reserves as an important element in confronting radical narratives, both from within and without Islamic tradition. It stands as an attempt to create moderate Muslim subjects who persistently uphold principles of inclusivity and transformative learning through opened-deliberation -rather than indoctrination- in educational settings.